Optimisation of thermal baffle for liquid metal injection nozzle. (2016) - Vinod, V.; Sreedhar, B.K.; Padmakumar, G.; Rajan, K.K.
SADHANA is a test facility dedicated for the experimental demonstration of passive safety grade decay heat removal in the prototype fast breeder reactor. Experiments are planned in SADHANA to characterise the behaviour of this system followed by various reactor transients. For simulating the reactor transients of hot pool, cold sodium at 310°C has to be injected to the test vessel of SADHANA at 550°C temperature. Thermal baffle provided in the nozzle of test vessel was optimised to limit the peak local stress. This paper gives the thermo-mechanical studies conducted to optimise the nozzle geometry with thermal baffles.